Ali Riaz’s ‘More than meets the Eye’ and a writer’s responsibility - Hasan, Md. Mahmudul (2022)
Writers and intellectuals are obligated to discuss the conditions of their fellow human beings. They embody the sensitive, artistic conscience of their people. It is their responsibility to stir moral indignation at gross injustices and the plight of the masses. Readers in return receive a cathartic pleasure after reading what the writer has said about them. In "African Literature and Social Problems" (1975), Romanus Egudu states that through depicting people's difficulties, writers provide readers with "intellectual pleasure in the midst of tears".